Língua brasileira de sinais na formação do profissional da saúde: a equipe de enfermagem - Viana Filho, Marco Aurélio Tupinambá (Universidade Federal de São Carlos, 2020)
The present research is based on two aspects, which are: first, the incipience of investigations and research on the causes of the difficulties of the Deaf to access health services and second, the influence of academic training in the care of the nursing professional. Thus, the main objective is to analyze the curricular matrix of the Nursing course of public HEIs in all regions of Brazil, to verify the presence and type of availability of the Libras curricular unit. The specific objectives are based on: analyzing the availability of the Libras curricular unit in the HEI courses; discuss the inclusion of the Libras curricular unit in the curriculum; to investigate how the Deaf care is provided by the nursing team in Primary Health Care and to analyze the implications for the health of the Deaf when interviewing the nursing team and Deaf patients. The participants studied were 41 nurses and nursing technicians, who are on the front line of the PHC, and 7 Deaf people who enjoy this service. As a complement and to understand the possible origin of the results, documental research was used to analyze the curricular matrix in search of the Libras curricular unit of all face-to-face courses offered by public HEIs in Brazil. Data analysis demonstrates that the health care of the Deaf patient is precarious, largely due to the poor training of health professionals. Most of the HEIs offer the course unit of Libras as an option and in some states it is still not available even 15 years after the Decree that prioritizes it.
Brazilian sign language in the academic education of health professionals: the nursing team
Keywords: Educação Especial; Língua Brasileira de Sinais; Formação profissional; Atendimento do Surdo à Saúde; Equipe de Enfermagem; Special Education; Brazilian Sign Language; Professional qualification; Health Care for the Deaf; Nursing Team; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO